USULAN RANCANGAN FOCUSED FACTORY DAN TATA LETAK FASILITAS DENGAN PENDEKATAN VIRTUAL CELL MANUFACTURING UNTUK KOMPONEN PESAWAT NC212I PADA DEPARTEMEN MACHINING PT DIRGANTARA INDONESIA - Jumaldi, Zulfa
Quality, cost, and delivery (QCD) are several indicators in assessing the production process of aircraft in PT Dirgantara Indonesia (PT DI). In 2020-2023, PT DI increased the demand for NC212i aircraft from 2 units to 6 units per year. Referring to QCD indicator, the challenge for PT DI to meet the demand according to the delivery deadline. This is because in the period of October 2019, there is a difference in process achievement with target production in the range of 6%-50% in the area of component assembly that is influenced by the low value of % on time delivery (% OTD) from the area of detail part manufacturing especially machining department, namely by 35.8%. Low % OTD is a result of a large proportion of setup time, which is 41.14% of the total processing time, so it affects the production lead time, for 266.199 hours or 16.637 days. An alternative solution developed to reduce the proportion of setup time is to dedicate facilities to producing NC212i or focused factory planes and improve the layout facilities. This research aims to calculate the needs of machine capacity and utilization in a focused factory application plan as well as designing the layout of facilitias with objective to reduce the proportion of setup time and production lead time. The layout design of the facility is done by a virtual cell manufacturing (VCM) approach where the availability of machines (machine based) as the only resources considered (single resource constraint). The VCM design was completed using a linear programing method of analytic with the maximal goal of total productive time and the minimum number of shared machines that resulted in decreased proportion of setup time. The planned implementation of the focused factory requires 37 workstations where the 35 types are machine workstations with the number of machines as many as 64 units. There are 6 types of machines with utilization value less than 10% and 16 engine type more than 50%. The result of the layout design of the facility with the VCM method can classify 107 component representations of a total of 1949 types of components and 29 machine types into seven part family and seven virtual cell manufacturing. The results of the grouping can reduce the setup time by 12.08% with contributions to decreased lead time by 4.20% from 266.199 hours to 255.03 hours.